Implementation of Cooperative Accountability in Managing Financial Reports at SMP Negeri 14 Binjai - Khoirul Abdi (Journal Markcount Finance, 2023)
This study aims to explore how cooperatives in SMP Negeri 14 Binjai implement accountability in preparing financial reports. The researcher's observations found several obstacles faced by the cooperative. One of them is the lack of counseling from the Binjai Cooperative Office because the SMP Negeri 14 Binjai cooperative does not yet have a legal entity. However, prior to the formation of this cooperative, the previous experience of the Binjai 11 Public Middle School cooperative which was already a legal entity had learned about accountability. The preparation of financial reports in this cooperative is monitored by the chairman of the cooperative and the supervisor of the cooperative. Good accountability implementation will have an impact on the preparation of financial reports in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). If human resources (HR) are able to prepare financial reports in accordance with SAK ETAP, then financial problems can be minimized, so that inspection and supervision of financial reports will be easier. This study uses qualitative research methods with primary data sources collected through interviews. The results showed that the financial reports at SMP Negeri 14 Binjai were compiled daily based on the income earned by the cooperative. The preparation of the financial statements is based on the application of basic standards and the balance sheet is prepared according to the simple accruals principle. The Semplas Sejahtera Cooperative, SMP Negeri 14 Binjai has presented its financial reports properly, as shown in the interviewees who stated that the cooperative's financial statements are presented in accordance with the transactions that occurred in one period. The presentation of these financial reports is related to cooperative finance and can be seen through the accountability reports submitted at the Annual Member Meeting (RAT) with assistance and supervision from supervisors.